(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article provides a comprehensive analysis of the theoretical foundations, legal mechanisms, and contemporary challenges related to a child’s right to lineage in Islamic law. It examines the concept of lineage from an Islamic perspective and highlights its significance in the Qur’an and Sunnah. Particular attention is given to the role of lineage in shaping personal identity and maintaining social stability. The study further analyzes key Islamic legal mechanisms designed to protect lineage, including marriage, li‘an (mutual imprecation), iddah (waiting period), denial of lineage, and adoption. In addition, through a textual analysis of primary Islamic sources, the article explores the legal importance of lineage and its relevance in contemporary society.